Antiperiodic Solutions for Liénard-Type Differential Equation with p-Laplacian Operator. (25th August 2010) - Chen, Taiyong; Liu, Wenbin; Yang, Cheng
Abstract : The existence of antiperiodic solutions for Liénard-type and Duffing-type differential equations withp -Laplacian operator has been studied by using degree theory. The results obtained improve and enrich some known works to some extent.